Development, optimization and application of a universal fluorescence multiplex PCR-based assay to detect BCOR genetic alterations in pediatric tumors - Meng Zhang; Xingfeng Yao; Nan Zhang; Yongbo Yu; Chao Jia; Xiaoxing Guan; Wenjian Xu; Xin Ni; Yongli Guo; Lejian He (Diagnostic Pathology)
Abstract Background A number of genetic aberrations are associated with the BCL6-correpresor gene (BCOR), including internal tandem duplications (ITDs) and gene fusions (BCOR::CCNB3 and BCOR::MAML3), as well as YWHAE::NUTM2, which are found in clear cell sarcoma of the kidney (CCSK), sarcoma with BCOR genetic alterations, primitive myxoid mesenchymal tumor of infancy, and high-grade neuroepithelial tumors in children. Detecting these gene aberrations is crucial for tumor diagnosis. ITDs can be identified by Sanger sequencing or agarose gel electrophoresis. However, gene fusions are usually detected through reverse transcription-polymerase chain reaction (RT-PCR) or fluorescence in situ hybridization. Methods that analyze these variants simultaneously in a sensitive and convenient manner are lacking in clinical practice. Methods This study validated a Universal Fluorescence Multiplex PCR-based assay that assessed BCOR ITDs, BCOR::CCNB3, BCOR::MAML3 and YWHAE::NUTM2 fusions simultaneously. Results The assay achieved a detection threshold of 10 copies for fusion genes and 0.32 ng genomic DNA for BCOR ITDs. The performance of this assay was also tested in a cohort of 43 pediatric tumors (17 undifferentiated small round cell sarcomas, and 26 tumors with a histological diagnosis of CCSK). In total, 20 BCOR ITDs, 4 BCOR::CCNB3 and one YWHAE::NUTM2 were detected. When compared with the final diagnosis, the assay achieved 93% sensitivity and 100% specificity. Conclusions Accordingly, this assay provided an effective and convenient method for detecting BCOR- and YWHAE-related abnormalities in tumors.